A Label-Free Fluorescent AND Logic Gate Aptasensor for Carbohydrate Antigen 15-3 Detection Based on Graphene Oxide - Hu, Wenxiao; Dong, Yafei; Wang, Luhui; Wang, Yue; Qian, Mengyao; Xi, Sunfan (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Molecular logic gate always makes use of fluorescent dyes to realize fluorescence signals. The labeling of the fluorophore is relatively expensive, resulting in low yield, and singly labeled impurities affect the affinity between the target and the aptamer. Label-free fluorescent aptamer biosensor strategy has attracted widespread interest due to lower cost and simplicity. Objective: Herein, we have designed an AND logic gate fluorescent aptasensor for detecting carbohydrate antigen 15-3(CA15-3) based on label-free fluorescence signal output. Materials and Methods: A hairpin DNA probe consists of CA15-3 aptamer and partly anti-CA15- 3 aptamer sequences as a long stem and G-rich sequences of the middle ring as a quadruplexforming oligomer. G-rich sequences can fold into a quadruplex by K+, and then G-quadruplex interacts specifically with N-methylmesoporphyrin IX(NMM), leading to a dramatic increase in fluorescence of NMM. With CA15-3 and NMM as the two inputs, the fluorescence intensity of the NMM is the output signal. Lacking CA15-3 or NMM, there is no significant fluorescence enhancement, and the output of the signal is “0”. The fluorescence signal dramatically increases and the output of the signal is “1” only when CA15-3 protein and NMM are added at the same time. Results: This biosensor strategy was observed to possess selectivity and high sensitivity for detecting CA15-3 protein from 10 to 500 U mL-1 and the detection limit was found to be 10 U mL-1, which also showed good reproducibility in spiked human serum. Conclusion: In summary, the proposed AND logic gate fluorescent aptasensor could specifically detect CA15-3.
Keywords: label-free detection